Exploring the Relationship between School Climate and Academic Motivation of Secondary School Students - Shahid Ullah; Dr. Muhammad Naseer Ud Din; Dr. Muhammad Nisar; Dr. Shah Jehan (Correspondence Author) (`, 2025)
The study investigated the relationship between school climate and academic motivation among secondary school students. A quantitative, correlational research design was employed, involving a sample of 200 students selected through stratified random sampling from secondary schools. Data were collected using two standardized instruments: the School Climate Scale (SCS) and the Academic Motivation Scale (AMS). Descriptive statistics indicated that students perceived their school climate as moderately positive and reported a moderately high level of academic motivation. Pearson’s correlation revealed a significant positive relationship between school climate and academic motivation (r = 0.58, p < 0.01). Multiple regression analysis further indicated that teacher support (β = 0.34, p < 0.001) and peer relationships (β = 0.29, p < 0.01) significantly predicted academic motivation, whereas school safety and fairness of rules were not significant predictors. These findings underscore the importance of relational aspects of school climate in enhancing students’ motivation. The study concludes that fostering teacher support and positive peer interactions can play a crucial role in motivating secondary school students. Recommendations are made for educators, school leaders, and policymakers to prioritize supportive relationships in educational settings. Keywords: school climate, academic motivation, teacher support, peer relationships, secondary school students